Role of Core Self-Evaluation Personality Trait and Individual Beliefs in Predicting Technology Acceptance Model 3 (TAM3) - Hannan Afzal; Farida Faisal; Munnawar Naz Khokharb; Nimra Javed (UW Journal of Management Sciences, 2022)
Purpose: This study attempts to empirically investigate the adoption of 3G/4G LTE technology in Pakistan. Methodology/Design: The data was collected using a structured questionnaire from consumers of twin cities of Pakistan. The sample was taken on basis of convenience sampling technique. Initially 700 questionnaires were distributed among the students, out of which 605 completely filled questionnaires were used for data analysis by using SPSS. Findings: The results for all variables were significant and showed positive relationship among them. The results reveal that core self-evaluation and trust have positive impact on technology acceptance model variables. Originality/Value: Based on TAM 3 theory the research formulated the theoretical framework, and then investigating the impact of core self-evaluation personality traits and individual belief trust on perceived ease of use and perceived usefulness to elucidate the individual’s adoption intention towards 3G/4G LTE technology. More specifically, this study aims to extend the technology acceptance model 3. Implication: This study is expected to provide better information and understanding of the factors influencing consumer’s adoption intention about 3G/4G LTE technology. It provides important implications for the marketers and retailers. Retailers and marketers are advised to observe personality and trustworthiness beliefs of target consumers and carefully judge their intention towards 3G/4G LTE technology. Easy to use and useful technology might have a stronger chance for adoption. Limitations: This study was limited to university students and to 3G/4G LTE technology.